Comparative Policy Analysis of PV Industry Development: Case Studies of China and the United States - Fu, Huijie (Transactions on Economics, Business and Management Research, 2024)
With global climate change, energy issues have evolved into critical global concerns. The development and utilization of new energy sources have garnered widespread attention, making large-scale advancements imperative. Solar photovoltaics, as one of the more mature sectors within the new energy landscape, have been particularly notable in recent years. By 2024, numerous countries have established comprehensive legal frameworks and policies for the new energy industry, forming robust industrial systems. Despite the rapid development of the solar photovoltaic industry, numerous challenges persist. This article examines the development conditions and current state of the solar photovoltaic industry in China and the United States, focusing on three key aspects: economy, policy, and technology. By comparing and analyzing these dimensions, this study aims to identify similarities and differences between the two countries, explore the underlying reasons, and evaluate the strengths and weaknesses of each nation's solar photovoltaic sector through quantitative analysis. Based on this analysis, this study will make predictions regarding future developments. Finally, this study will provide a well-founded outlook on the future of the solar photovoltaic industry in China and the United States.